1978
DOI: 10.1111/j.1095-8649.1978.tb03447.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polychlorinated biphenyls on plasma steroid levels and hepatic microsomal enzymes in fish

Abstract: Aroclor 1254 was administered intraperitoneally (25 mg kg body wt-I in 1 ml of arachis oil) at weekly intervals for 4 weeks to trout and carp; arachis oil was used as the control. Activities of the following hepatic microsomal enzymes, aminopyrine demethylase, pnitroreductase, UDP-glucuronyl-transferase and I-leucyl-P-naphthylamide splitting enzyme were measured in both species; cytochrome P460 and microsomal protein contents were also determined.The changes in the levels of androgens, oestrogens and corticoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

1987
1987
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…Median concentrations of E2 in male and female carp were inversely correlated with sediment PCB residues in Woods Pond, Massachusetts (Smith et al, 2002). Antiandrogenic and PCBs, HG, and endocrine disruption in Hudson fish antiestrogenic effects were observed in carp after four weeks of intraperitoneal injections of Aroclor 1254; concentrations of estrogens and androgens in blood of female and male were significantly reduced (Sivarajah et al, 1978a); developing oocytes became fragmented and spermatozoa were damaged (Sivarajah et al, 1978b).…”
Section: Relation Of Endocrine Biomarkers To Pcb Residuesmentioning
confidence: 99%
“…Median concentrations of E2 in male and female carp were inversely correlated with sediment PCB residues in Woods Pond, Massachusetts (Smith et al, 2002). Antiandrogenic and PCBs, HG, and endocrine disruption in Hudson fish antiestrogenic effects were observed in carp after four weeks of intraperitoneal injections of Aroclor 1254; concentrations of estrogens and androgens in blood of female and male were significantly reduced (Sivarajah et al, 1978a); developing oocytes became fragmented and spermatozoa were damaged (Sivarajah et al, 1978b).…”
Section: Relation Of Endocrine Biomarkers To Pcb Residuesmentioning
confidence: 99%
“…These changes in reproductive steroid hormones have not been directly linked to MFO induction, but seem to be related to multiple breaks in the hypothalamo-pituitary-gonadal axis controlling reproduction . Despite the inability to directly correlate MFO induction with steroid depression (Munkittrick et al, 1994a), additional recent work has shown that depressions in steroid hormone production or reproductive performance can occur after exposure to a variety of other compounds associated with MFO induction, including some pesticides (Munkittrick et al, 1994b), PCBs (Freeman & Idler, 1975;Sivarajah et al, 1978;Thomas, 1988Thomas, , 1990Greeley et al, 1993;Kidd et al, 1993) and PAHs (Truscott et al, 1983;Thomas, 1988Thomas, , 1990McMaster et al, 1995b).…”
Section: Introductionmentioning
confidence: 99%
“…We have observed this biphasic cortisol response to chronic stress previously (Pottinger, Prunet and Pickering, unpublished) but had ascribed the phenomenon to interrenal exhaustion. In trout and carp subject to treatment with an organic compound, Aroclor 1254, UDP-glucuronyltransferase (UDPGT) levels increased, and concomitant with the increased activity of the conjugating enzymes a decrease in plasma steroid levels, including corticosteroids, was noted (Sivarajah et al 1978). Similarly, increased accumulation of [ 3 H]estradiol was observed in the bile of rainbow trout in which UDPGT levels had been elevated by treatment with -naphthoflavone (Forlin and Haux 1985).…”
Section: Discussionmentioning
confidence: 93%